Pengaruh Gaya Hidup, Varian Produk Dan Layanan Terhadap Keputusan Pembeli Di Lucha Coffe Medan Johor - batubara, mutia syahreza; Syafina, Wan Dian; Hidayat, Toni; Siregar, Horia (Movere Journal, 2025)
The purpose of this study was to analyze lifestyle, product variants and services affect buyer decisions at Lucha Coffee Medan Johor. This type of research is quantitative. The population in this study were 390 people who made purchases at Lucha Coffe Medan Johor which were taken from data in April 2024. In this study, the sample was taken using the Slovin formula, and using random sampling techniques. So, the total number of respondents in this study was rounded up to 80 consumers who made purchases at Lucha Coffee Medan Johor. The research instrument used a questionnaire with a Likert Scale data measurement scale. The data analysis technique uses validity, reliability and classical assumption tests. The data analysis method uses multiple linear regression with the help of the SPSS program. The results of this study indicate that partially lifestyle has a positive and significant effect on purchasing decisions at Lucha Coffee Medan Johor. Product variants have a positive and significant effect on purchasing decisions at Lucha Coffe Medan Johor. Service has a positive and significant effect on purchasing decisions at Lucha Coffee Medan Johor. In addition, lifestyle, product variants and service simultaneously (simultaneously) affect the purchasing decision variable at Lucha Coffe Medan Johor with a value of Fcount (58.744) > Ftabel (2.72), and a significance value of 0.000 <0.05.